2020
DOI: 10.26629/ijmp.2019.07
|View full text |Cite
|
Sign up to set email alerts
|

Obturators to facilitate speech and swallowing in a maxillectomy patient with dementia and cerebral infarction

Abstract: The purpose of dental treatments normally includes the recovery from the functional impairments and aesthetic problems. This case report describes the rehabilitation of a maxillectomy patient with dementia and cerebral infarction, using obturators made of different materials to facilitate speech and swallowing. The patient had difficulty inserting the original prosthesis by himself and would sometimes bite down on the obturator to position it in his mouth instead of using his hands. As a result, the obturator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Maxillofacial prosthodontics provides prosthetic rehabilitation for functions such as speech, swallowing, mastication, and esthetics and is a well-recognized subspecialty of prosthodontics [ 1 , 2 , 3 ]. In 2018, Yanagi et al conducted a study at the Clinic for Maxillofacial Prosthetics, Tokyo Medical and Dental University, and found that the average age of patients had shown an increasing trend over the previous 35 years and that almost 80% of patients had developed tumors in Japan’s now super-aging society [ 4 ], and we feel that this could be even higher now.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Maxillofacial prosthodontics provides prosthetic rehabilitation for functions such as speech, swallowing, mastication, and esthetics and is a well-recognized subspecialty of prosthodontics [ 1 , 2 , 3 ]. In 2018, Yanagi et al conducted a study at the Clinic for Maxillofacial Prosthetics, Tokyo Medical and Dental University, and found that the average age of patients had shown an increasing trend over the previous 35 years and that almost 80% of patients had developed tumors in Japan’s now super-aging society [ 4 ], and we feel that this could be even higher now.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the structure of maxillofacial prostheses is quite unique compared with general prostheses, and the oral cavity is sensitive and prone to bleeding, especially in maxillectomy patients. Sumita et al reported a case in which a maxillectomy patient experienced difficulty inserting his maxillary obturator prosthesis after developing cerebrovascular disease and dementia [ 3 ]. However, there has been no report on the actual situation of patients who need maxillofacial prosthetic treatment from the perspective of dementia and patient-reported difficulty of inserting prostheses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation